MIMO Dielectric Resonator Antennas for 5G Applications: A Review - Ahmad, Hamza; Jamaluddin, Mohd Haizal; Che Seman, Fauziahanim; Rahman, Muhibur (Mdpi, 2023)
This article presents a thorough literature review of published designs of multiple-input multiple-output (MIMO) dielectric resonator antennas (DRAs) specifically designed for 5G applications. The performance of these designs is discussed in detail, considering various parameters such as gain, isolation, size, bandwidth, profile, and radiation characteristics. The primary objective of this work is to appreciate the significant progress made in this vital area of research. This article also aims to identify any existing gaps in the literature and provide potential directions for future work.